Will Elders Provide for Their Grandchildren? : Unconditional Cash Transfers and Educational Expenditures in Bolivia - Canavire-Bacarreza, Gustavo (World Bank, Washington, DC, 2017)
This paper takes advantage of repeated cross-section household surveys and a sharp discontinuity created by the introduction of an unconditional cash transfer to elders. The paper evaluates the impact of these cash transfers on the educational expenditures for children within a household. The analysis finds positive and significant effects of the program at the aggregate level. It also finds that the program has stronger effects in indigenous populations and among female and rural populations. The results are robust with respect to a series of falsification tests, survey structures, model specifications, and estimation methods.